Conservation Design and Scenario for Flood Mitigation on Arui Watershed, Indonesia - Mahmud Mahmud; Ambar Kusumandari; Sudarmadji Sudarmadji; Nunuk Supriyatno (Faculty of Geography, Universitas Gadjah Mada, 2019)
Flooding has been natural disaster in Indonesia and elsewhere. This research is designed to create scenarios and designs conservation to mitigate flooding disaster. Data potential ,vulnerability, and duplicated river covering 0.25% of the targeted flooding area were collected and analysed. Five disain of conservation, natural river as control, river normalization, normalization with gabion stone, river straigtening, and straigtening with gabion stone, are proposed, and main targeted responses of these five scenarios are river current velocity. Effectiveness scenarios were analysed using Anova and Tukey test. The results showed that alignment with gabion stone was the most effective scenario for flooding mitigation since this was the most effective in increasing river current velocity. This could prevent riverbank occurrence of avalanche, accelerate river current, overcome flooding, and prevent future flooding. Other scenarios likes dead clicth ended-hallway, canalization, and riparian reclamation are also possible implemented.